Categories of Critical Thinking in Information Managent. A study of Critical Thinking in decision making processes - Haase, Fee-alexandra (Nómadas. Critical Journal of Social and Juridical Sciences, 2010)
This article focuses as a survey on the qualities of Critical Thinking on reviewing its definitions in recent history of academic research and compared to other intellectual processes. On the one hand we will compare the basic characteristic qualities of Critical Thinking with other types of thinking. On the other hand we will give examples how Critical Thinking is a part of the decision making processes both in personal human issues and institutional decision making processes. Since Critical Thinking is an intellectual skill, we show the applications of this intellectual skill within contemporary life. Critical Thinking has several academic roots of philosophy, rhetorical argumentation, logic and social science, but also is an auxiliary tool in other academic disciplines. Coming from these roots Critical Thinking also finds its applications in contemporary private and professional life. Based on this historical and exemplifying discourse of criticism, we will argue for a general importance of Critical Thinking contrary to contemporary predominance as an applied skill and educational tool.